488 NOVEL POTASSIUM BINDERS IMPROVES RAASI THERAPY OPTIMIZATION IN HEART FAILURE: A SYSTEMATIC REVIEW AND META-ANALYSIS. (15th December 2022) - Esposito, Immacolata; Dell´aversana, Simona; Basile, Christian; Chirico, Alfonsina; Colella, Angela; Ambrosio, Antonio; Esposito, Gennaro; Marzano, Federica; Amato, Chiara; Gargiulo, Paola; Perrone-filardi, Pasquale; Paolillo, Stefania
Abstract: Background: Hyperkalemia (HK) often occurs among patients with heart failure (HF), particularly when treated with renin-angiotensin-aldosterone system inhibitors (RAASi). Even modest variations from normal potassium levels raise the risk of mortality and prompt patients to limit or cease disease-modifying treatment. Novel potassium binders (NPB), patiromer and sodium zirconium cyclosilicate, are approved for treatment of HK, but whether this results in a real optimization of HF treatment remains to be seen. Objectives: To assess the efficacy of NPB on the persistence of therapy with RAASi in HF patients. Methods: PubMed and Web of Science were searched without restrictions from inception to 06 August 2022 to identify valuable articles. The studies that met the inclusion criteria were analyzed. The prespecified main outcome was the proportion of HF patients achieving target dose of RAASi. Secondary outcomes were the reduction in potassium levels, hyperkalemia events and persistence of therapy with RAASi in the overall population. Results: Eight studies, with a total of 2247 patients were included. NPB improved optimization of RAASi therapy in HF compared to placebo by 21% (95% CI: 5% – 39%), decreased potassium levels by 0.48 mEq/L (95% CI: 0.28–0.67) and decreased hyperkalemia events by 53% (95% CI: 34% – 64%) and improved the proportion of the overall study population on RAASi therapy by 28% (95% CI: 7% – 52%). Conclusion: The present meta-analysis suggests that NPB are favorable in improving the proportion of patients on RAASi therapy, whether they have HF or not, in reducing potassium levels and hyperkalemia events.